The effects of TRX exercises on the stabilizer muscles of women involved in recreational fitness - Tsipin L.L.; Zakharov F.E.; Samsonov M.A.; Shorikov M.S. (Theory and Practice of Physical Culture, 2023)
Abstract Objective of the study was to determine the degree of force impact of various TRX exercises on the stabilizer muscles of women involved in health fitness. Methods and structure of the study. The experiment was conducted at the “Gravitation” fitness club, St. Petersburg. The study involved six women aged 38-45 years with different ratios of stabilizing muscle strength. Electrical activity was recorded in eight stabilizer muscles of the trunk and lower extremities while performing 17 common TRX exercises. Muscle electrical activity was recorded using the Delsys Trigno™ wireless system (Delsys Inc.). Using electromyography data, the strength developed by the muscles was indirectly assessed and TRX exercises were determined that had the greatest impact on individual stabilizer muscles. Results and conclusions. Different directions and degrees of impact of TRX exercises on stabilizer muscles have been established. Complex impact exercises include “Diagonal twisting” and “Pica”, during which the relative electrical activity, characterizing the force developed, for the rectus and external oblique abdominal muscles, rectus femoris, trapezius and iliopsoas muscles ranges from 68.4% to 94.1%. The exercises that have the greatest selective impact include: for the rectus abdominis muscle – “Saw”, for the external oblique abdominal muscle – “Pike”, for the rectus femoris muscle – “Twisting”, for the biceps femoris muscle – “Plank on the back”, for the middle for the gluteal muscle – “Leg extension in a supine plank”, for the trapezius muscle – “Reverse plank”, for the iliopsoas muscle – “Pike”, for the quadratus lumborum muscle – “Side plank”. When performing these exercises, the relative electrical activity of the muscles is more than 80%. The obtained patterns must be taken into account when developing methods for correcting the physical fitness of women involved in health-improving fitness using TRX exercises.